Interference of the Histone Deacetylase Inhibits Pollen Germination and Pollen Tube Growth in Picea wilsonii Mast. - Yaning Cui; Yu Ling; Junhui Zhou; Xiaojuan Li (PLoS ONE, 2015)
Histone deacetylase (HDAC) is a crucial component in the regulation of gene expression in various cellular processes in animal and plant cells. HDAC has been reported to play a role in embryogenesis. However, the effect of HDAC on androgamete development remains unclear, especially in gymnosperms. In this study, we used the HDAC inhibitors trichostatin A (TSA) and sodium butyrate (NaB) to examine the role of HDAC in Picea wilsonii pollen germination and pollen tube elongation. Measurements of the tip-focused Ca2+ gradient revealed that TSA and NaB influenced this gradient. Immunofluorescence showed that actin filaments were disrupted into disorganized fragments. As a result, the vesicle trafficking was disturbed, as determined by FM4-64 labeling. Moreover, the distribution of pectins and callose in cell walls was significantly altered in response to TSA and NaB. Our results suggest that HDAC affects pollen germination and polarized pollen tube growth in Picea wilsonii by affecting the intracellular Ca2+ concentration gradient, actin organization patterns, vesicle trafficking, as well as the deposition and configuration of cell wall components.